Tc4, a Caenorhabditis elegans transposable element with an unusual fold-back structure. - Yuan, J Y (1991)
We have identified and characterized a family of transposable elements in the nematode Caenorhabditis elegans. The Tc4 transposable element family is present at about 20 copies per haploid genome in the C. elegans Bristol and Bergerac strains. Although Tc4 transposition events have not been observed in these wild-type strains, we have identified Tc4 transposition events in the mut-2 mutant strain TR679, in which the elements Tc1 and Tc3 also transpose at a higher frequency than in the wild type. We determined the sequence of one Tc4 element. This 1.6-kilobase element contains almost perfect inverted terminal repeats of 774 base pairs (bp) with a 57-bp unique internal sequence. Tc4 is a fold-back element, but its long inverted terminal repeats, unlike those of the fold-back elements of other organisms, do not consist of multiple short repeats. In the two cases studied, Tc4 insertion resulted in duplication of a TNA trinucleotide target site. The family of Tc4 elements differs from other C. elegans transposable element families in structure, degree of structural heterogeneity, and target-site specificity.